Reinternalisasi NDP dalam Perikemanusiaan sebagai Representasi Kecintaan kepada Tuhan - Fitri (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2022)
Maturity of religious understanding is a major effort to achieve religious harmony in Indonesia. Muslim Students Association (Himpunan Mahasiswa Islam)’s Core Values of Struggle is the starting point to develop, to disseminate and to implement the religious maturity. At least, there are three aspects of its core values that important to achieve religious harmony in Indonesia, namely: Monotheism, the humanitarian aspects and social aspects. These three aspects will bring interfaith relations more open, tolerant and harmonious. Religious people fully realize that all men are ungodliness in the same God, the Almighty God, all religious people are given the freedom to understand, to appreciate and to practice their religion in full conviction. Religious people also should to believe that all human beings are basically good so that they can view a positive and optimistic attitude to other religious believes, instead of being suspicious of one another. Furthermore, inter-religious relations need the real cooperation in everyday life. All religions need cooperation against common enemies, those are social injustice, poverty, ignorance, violations of human rights and the tyranny that alienates the awareness of God. All religions have a responsibility to the real work.